Pengaruh Emotional Value dan Social Value pada Minat Pembelian Online - Rena Feri Wijayanti; Lina Budiarti (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
The development of consumer shopping patterns has shown a phenomenon where activities went through online. This study focuses on examining the behavior of consumers' interest in making purchases by looking at the influence of socio-physiological value aspects, namely social value ??, and emotional values. The process of collecting data by distributing questionnaires to the consumer in the Generation Z category is based on purposive sampling. Multiple Linear Regression was used to analyze the data. The result that online purchase intention has explained from the variables included in the emotional and social value has the contribution of 44.1%.